Personality Traits in Latin America: A Cross-Cultural Study of the Big Five Factor Structure and its Relationship with Self-Reported Daily Behaviors - Cupani, Marcos (2024)
Fil: Cupani, Marcos. Universidad Nacional de Córdoba. Facultad de Psicología; Argentina.